Antioxidant activities of Pandanus amaryllifolius leaves extracted under four designed extraction conditions - Thatsanasuwan, Natthaphon; Srichamnong, Warangkana; Chupeerach, Chaowanee; Kriengsinyos, Wantanee; Suttisansanee, Uthaiwan (Food and Applied Bioscience Journal, 2017)
Pandanus amaryllifolius is a tropical plant in Pandanaceae family, which customarily used for food coloring and flavoring. Leaves of P. amaryllifolius provide a rich source of essentials oil, carotenoid, vitamin E and other bioactive compounds such as antioxidants. High quantity of total phenolic compounds (TPC) and antioxidants (as being detected by 2,2-diphenyl-1-picry hydrazyl radical (DPPH) and linoleic acid peroxidation methods) were previously reported. Nevertheless, limited information on antioxidant activities of P. amaryllifolius leaves regarding extraction conditions is available. Thus, the purpose of this study was to investigate the effect of extraction conditions of P. amaryllifolius leaves regarding its antioxidant activity. Freeze-dried powder of P. amaryllifolius leaves were extracted under designed extraction conditions including extraction times (15–240 minutes), concentrations of aqueous ethanol (0–100% v/v), extraction temperatures (30–90°C) and solid-to-liquid ratios (1:20–1:60 v/w). The antioxidant activities were measured using ferric reducing antioxidant power (FRAP) method. As results, it was found that the antioxidant activities of P. amaryllifolius leaves extracted under investigated experiments were ranged from 9.54–23.16 mg trolox equivalent (TE) per 1 g dry weight. The optimized extraction conditions of P. amaryllifolius leaves were 15 minutes of extraction time, 80% (v/v) aqueous ethanol, and 1:60 (v/w) of solid-to-liquid ratio, while extraction temperature was an insignificant factor for extraction conditions. The information received from this research would support further investigation on optimized of condition for extraction by using response surface methodology and isolation of bioactive compounds from leaves of P. amaryllifolius.